2002
DOI: 10.1080/152873902753396802
|View full text |Cite
|
Sign up to set email alerts
|

Prolongation of Human Neutrophil Survival by Low-Level Mercury via Inhibition of Spontaneous Apoptosis

Abstract: Low levels of organic and inorganic mercury compounds have been reported previously to induce cell death by apoptosis in human peripheral blood mononuclear cells (MNC). but little is known about their potential effects on the viability and death of polymorphonuclear neutrophils (PMN). In contrast to MNC, PMN are known to undergo readily spontaneous apoptosis both in vivo and in vitro. Therefore, it was hypothesized that PMN may differ from MNC in their reactions to low mercury levels. The effects of methylmerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…In the Faroes, total mercury concentrations in blood and hair primarily indicate exposures to methylmercury [38], thus suggesting that different chemical speciations may affect the mercury-associated toxicity. Mercury-induced cytotoxicity has been demonstrated in cells of the immune system, including B cells, T cells, and monocytes [39, 40], and two in vitro studies demonstrated that Hg exposure causes mitochondrial dysfunction and enhances the apoptosis of neutrophils and mononuclear cells including T cells [41, 42]. However, mercury has also been shown to exert immunomodulatory and anti-apoptotic effects in animals [43] and to be associated with autoimmune diseases in both animals and humans [44].…”
Section: Discussionmentioning
confidence: 99%
“…In the Faroes, total mercury concentrations in blood and hair primarily indicate exposures to methylmercury [38], thus suggesting that different chemical speciations may affect the mercury-associated toxicity. Mercury-induced cytotoxicity has been demonstrated in cells of the immune system, including B cells, T cells, and monocytes [39, 40], and two in vitro studies demonstrated that Hg exposure causes mitochondrial dysfunction and enhances the apoptosis of neutrophils and mononuclear cells including T cells [41, 42]. However, mercury has also been shown to exert immunomodulatory and anti-apoptotic effects in animals [43] and to be associated with autoimmune diseases in both animals and humans [44].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we have found that tributyltin (TBT) can induce neutrophil apoptosis (18). Intriguingly, mercury was found to delay or induce neutrophil apoptosis, depending on the concentration used and the duration of treatment (34).…”
Section: Discussionmentioning
confidence: 94%
“…Our finding of apoptosis resistance of neutrophils induced by Hg strengthens recent in vitro evidence of the preventive effect of Hg on neutrophil cell death. (28,29) It is plausible that our described severe loss of B cells induced by Hg may lead to permanent unbalance in the repertoire of antibody-producing cells. This is important because cell interactions among members of a complete repertoire of B lymphocytes are required for the suppression of pathogenic autoimmune reactivities.…”
Section: Discussionmentioning
confidence: 97%